The nexus of United Nations' 2030 Agenda and corporate sustainability reports. (22nd September 2022) - Tsalis, Thomas A.; Terzaki, Maria; Koulouriotis, Dimitrios; Tsagarakis, Konstantinos P.; Nikolaou, Ioannis E.
Abstract: The role of corporate responsibility in the protection of the natural environment is unquestionably a key factor in achieving a stable and sustainable future for modern economies and societies. Thus, the business community implements practices to protect the natural environment and eliminate its negative impacts. Such corporate practices are placed under the umbrella of the sustainable development concept which pursues multifaceted economical environmental and social goals and more recently the 17 sustainable development goals (SDGs) of the United Nations' (UN) 2030 Agenda. In this context, this paper aims at examining corporate reporting behavior in the energy sector in relation to SDG disclosures during the first years of the introduction of Agenda 2030. An assessment framework was designed to assess the quality and the range of information disclosed in a set of 105 sustainability reports published during the period 2016–2018. The findings of the empirical analysis led to the conclusion that the examined energy firms did not provide an adequate level of information regarding corporate actions toward the 2030 Agenda for sustainable development. Both the quality of disclosed information and the number of disclosure topics were low. SDG4 was the main focus of the reports, with the highest reporting performance, whereas the issues covered by SDG16 and SDG1 were discussed the least in the examined reports. Also, in practical terms, the proposed methodology provides a sound basis for further investigation of the sustainability reporting practices from the energy sector in relation to the scope of SDG.